Prostaglandin biosynthesis by guinea-pig skeletal muscle in vitro and the effect of oestradiol-17 beta and progesterone. - Kerry, P J (1979)
1. The effect of oestradiol and progesterone on prostaglandin biosynthesis by guinea-pig skeletal muscle in vitro has been investigated. 2. At high concentrations, oestradiol-17 beta (100 microgram/ml) and progesterone (500 microgram/ml) increased prostaglandin E and prostaglandin F synthesis (measured by radioimmunoassay). 3. It is suggested that these steroids are unlikely to be found in vivo at levels sufficient to influence prostaglandin synthesis by skeletal muscle in physiological and pathological situations.